Detection of Hydroureter in Rat After Medial and Distal Unilateral Ureteral Obstruction Using Ultrasound Frequency 10 MHz - Rickyawan, Nofan; Arifianto, Dinar; Adji, Dhirgo (Faculty of Veterinary Medicine Universitas Brawijaya, 2019)
Unilateral ureteral obstruction can occur in all animals and it is located proximal, medial and distal. Obstruction causes abnormalities in ipsilateral ureters in the form of hydrouterers. The aim of this study was to detect hydroureters in post-unilateral medial and distal ureteric rats using a 10 MHz ultrasonography frequency. Thirty-six female Sprague Dawley rats aged 3 months were divided into 3 treatment groups. Each group consisted of 12 individuals. Group I as a control received laparotomy treatment. Group II laparotomy with medial right-hand ureteral ligation and group III with right distal ureteral ligation. Three rats taken randomly from each group at weeks 1, 2, 3 and 4 post-ligation is then performed ultrasonography. The results of ultrasonography were analyzed descriptively, comparatively but ureteral diameter were analyzed using statistical of 3x4 factorial patterns. Ultrasound examination showed that ligation in one ureter caused rat undergoing unilateral ureteral obstruction and hidroureter. The diameter of the ureter with a hydroureter has increased from the 1st to 4th week. The increase occurs because the urine in the lumen cannot be excreted. The contralateral ureter remains normal and cannot be observed. The conclusion of the study is that hydroureter in rats can be detected using the frequency of 10 MHz ultrasonography which is characterized by anekoic tubular formation posterior to the right kidney. The unilateral ureteral obstruction has no effect on the contralateral ureter because it is still able to compensate for the performance of the ipsilateral ureter that has a hydroureter. The difference in the location of ligation and time of examination affect the increase in ipsilateral ureteral diameter.